Evaluasi Kinerja Mentoring Pendidikan Agama Islam Tingkat SMA dengan Metode Importance Performance Analysis - Wasto; Endin Mujahidin; Imas Kania Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the era of globalization and digitalization, teenagers are easily exposed to various negative behaviors such as promiscuity, alcohol consumption and inappropriate content on the internet. This negative behavior has a negative impact on the development of adolescent character and morals. Islamic Religious Education (PAI) has a very important role in forming the character and morals of students, especially at the secondary school level. The problem is that the time allocation for PAI in public schools is very limited. The time provided for 2-3 hours of lessons a week is considered insufficient to cover all PAI material. Limited time for PAI learning in public schools is a challenge that requires a solution, namely PAI mentoring activities. The problem of PAI mentoring in schools lies in the match between expectations and the reality of implementation felt by participants. This research aims to evaluate the performance of PAI mentoring at SMAIT Ummul Quro Bogor. This research uses a type of responsive evaluation research model (Responsive Evaluation). The evaluation method uses Importance Performance Analysis (IPA). This science method aims to determine the level of conformity between interests and performance which is then plotted using a Cartesian diagram. The data collection technique was through a questionnaire involving 405 student participants as respondents. Data from the questionnaire results collected were tested for validity and reliability. Next, it was analyzed using the IPA method. The IPA calculation results have a suitability level of 101%, which means the level of satisfaction with mentoring performance is high. In the Cartesian diagram, of the 20 performance indicator attributes, there are 15 attributes whose performance is satisfactory, namely a comfortable mentoring room, effective implementation of mentoring, mentor mastery of the material, responsiveness to participant complaints, readiness to serve participants, maintaining personal confidentiality, creating a sense of security, image the school's positive attitude towards mentoring, providing self-confidence to participants, ease of obtaining information, sensitivity to attention to suggestions and criticism as well as service that does not differentiate between status, Mentor's appearance during mentoring, Quickly providing mentoring information, and Speed ​​of mentor responding to participants. However, there needs to be improvements and improvements, especially in the availability of mentoring consultation rooms, availability of mentoring modules, timely mentoring hours, mentors establishing intense communication with mentoring participants, and providing individual attention.